ChemInform Abstract: Aspulvinones from a Mangrove Rhizosphere Soil‐Derived Fungus Aspergillus terreus Gwq‐48 with Antiinfluenza A Viral (H1N1) Activity. Issue 32 (18th July 2013) - Gao, Huquan; Guo, Wenqiang; Wang, Qiang; Zhang, Lianqing; Zhu, Meilin; Zhu, Tianjiao; Gu, Qianqun; Wang, Wei; Li, Dehai
Abstract A new butenolide, isoaspulvinone E (I), is isolated along with two known butenolides from the marine derived fungus, Aspergillus terreus Gwq‐48.